Mitochondrial Transfer in Cardiovascular Disease: From Mechanisms to Therapeutic Implications - Jun Chen (Frontiers Media S.A., 2021)
Mitochondrial dysfunction has been proven to play a critical role in the pathogenesis of cardiovascular diseases. The phenomenon of intercellular mitochondrial transfer has been discovered in the cardiovascular system. Studies have shown that cell-to-cell mitochondrial transfer plays an essential role in regulating cardiovascular system development and maintaining normal tissue homeostasis under physiological conditions. In pathological conditions, damaged cells transfer dysfunctional mitochondria toward recipient cells to ask for help and take up exogenous functional mitochondria to alleviate injury. In this review, we summarized the mechanism of mitochondrial transfer in the cardiovascular system and outlined the fate and functional role of donor mitochondria. We also discussed the advantage and challenges of mitochondrial transfer strategies, including cell-based mitochondrial transplantation, extracellular vesicle-based mitochondrial transplantation, and naked mitochondrial transplantation, for the treatment of cardiovascular disorders. We hope this review will provide perspectives on mitochondrial-targeted therapeutics in cardiovascular diseases.